Penguatan Kompetensi Public Speaking Para Pendidik, Tenaga Kependidikan, Tenaga Penunjang Pendidikan dan Mahasiswa di Sekolah Polisi Wanita - Melda Yanny; Ananda Fauzi Harahap; Siti Nuri Nurhaidah; Istajib; Abdul Ghoni Purwanto Edi (Yayasan Cendekia Gagayunan Indonesia, 2025)
Community service activities through Public Speaking training at the Women's Police School (Sepolwan) are driven by the limited oral communication skills of prospective female police officers in delivering messages systematically, confidently, and persuasively. The goal of this activity is to enhance the public speaking competencies of Sepolwan students so that they can present themselves more professionally, humanely, and communicatively in carrying out their police duties. The methods used include participatory training through lectures, simulations, role plays, presentation practices, and reflective mentoring. The implementation results show a significant improvement in verbal skills (intonation, diction, clarity of message) as well as nonverbal skills (eye contact, expression, body language). Additionally, participants showed an increase in self-efficacy in facing audiences, courage to speak in public forums, and the ability to build communicative interactions. These findings reinforce the relevance of the theoretical framework. the communication competency theory and self-efficacy theory, while also affirming that public speaking training contributes to the formation of social institutions that support the role of policewomen as professional and humane public communicators.